Environmental impact and energy consumption of transport pavements in Cyprus - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Achilleos, Constantia; Kallis, Stelios; Neofytou, P.; Neocleous, Kyriacos; Pilakoutas, Kypros (My University, 2009)
This paper presents the results obtained for carrying out life cycle costing for an environmental impact and energy consumption for different transportation pavements used and proposed in the ‘Ecolanes’ project. EcoLanes is an FP6 STREP project, funded under the priority thematic area of Sustainable Surface Transport, FP6-2005-Transport-4 call 3B. The project develops infrastructure for surface transport using slip forming and roller compaction techniques based on existing asphalt laying equipment and steel fibre reinforced concrete. The benefits of the new construction concept will be manifold, such as to reduce construction costs by 10-20%, reduce construction time by 15%, reduce the energy consumption in road construction by 40%, minimize maintenance, use waste materials in road construction and make tyre recycling more economically attractive. Paphos District area in Cyprus is one of the selected areas in which a full-scale demonstration will be implemented. Gabi software is used to apply both environmental impact and energy consumption process. The method will be applied using all the available data during the construction phase of the pavement and several assumptions/projections will be made during the maintenance and demolition process. Results of the application of the proposed method using archived and recent data are presented in this pape
Keywords: Transport pavement; Energy consumption; Environmental impact; Asphalt; Life cycle costing; Tyre recycling